Association of vitamin D receptor gene haplotypes with late-onset Alzheimer's disease in a Southeastern European Caucasian population - Dimitrakis,E.; Katsarou, M. S.; Lagiou, M.; Papastefanopoulou,V.; Spandidos, D.A.; Tsatsakis, A.; Papageorgiou, S.; Moutsatsou, P.; Antoniou, K; Kroupis, C.; Drakoulis, N. (Exp.Ther.Med., 2022)
Vitamin D receptor (VDR) gene single nucleotide polymorphisms (SNPs) have been investigated over the past years with the aim of identifying any association with the development of Alzheimer's disease (AD). However, information regarding the potential association of VDR SNP haplotypes with AD is limited. The aim of the present study was to provide additional knowledge on the effects of VDR haplotypes on the development of late-onset AD in a cohort of Southeastern European Caucasians (SECs). The study sample included 78 patients with late-onset AD and 103 healthy subjects as the control group. VDR SNPs that were analyzed were TaqI (rs731236), BsmI (rs1544410) and FokI (rs2228570). The CAC (TaqI, BsmI and FokI) haplotype was found to be associated with a 53% lower risk of developing the disease (OR, 0.47; 95% CI, 0.23-0.96; P=0.04) and the TAC (TaqI, BsmI and FokI) haplotype was associated with an ~6-fold greater risk of developing AD (OR, 6.19; 95% CI, 1.91-20.13; P=0.0028). Female subjects carrying the TAC haplotype had a ~9-fold greater risk of developing AD in comparison to female control subjects (OR, 9.27; 95% CI, 1.86-46.28; P<0.05). The TaqI and BsmI polymorphisms were in high linkage disequilibrium (D'=0.9717, r=0.8467) and produced a haplotype with a statistically significant different frequency between the control and AD group. The TA (TaqI and BsmI) haplotype was associated with an ~8-fold greater risk of developing AD (OR, 8.27; 95% CI, 2.70-25.28; P<0.05). Female TA carriers had an ~14-fold greater risk of developing the disease in comparison to female control subjects (OR, 13.93; 95% CI, 2.95-65.87; P<0.05). On the whole, the present study demonstrates that in the SEC population, TAC and TA are risk haplotypes for AD, while the CAC haplotype may act protectively. SEC women carrying the TAC or TA haplotype are at a greater risk of developing AD, thus suggesting that women are markedly affected by the poor utilization of vitamin D induced by the VDR haplotype